Profiling Students' Linguistic Verbal Intelligence in Arabic Language Learning - Toifah, Nur; Ulum, Mohammad Samsul; Arifa, Zakiyah (Universitas Pendidikan Mandalika, 2025)
This research aims to explain the level of linguistic verbal intelligence of students who are studying Arabic, because it involves the ability to understand, use, and manipulate language effectively, both orally and in writing. This research uses a mixed method approach to describe students' linguistic verbal intelligence. Data was collected through the IST (Intelligence Structure Test) compiled by Rudolf Amthauer in 1953 in Frankfurt, Germany because the components in the structure are arranged hierarchically, where the dominant field will influence other fields, the dominant ability in the intelligence structure will determine and influence other abilities. It consists of parts that are interconnected in meaning (structure). Their linguistic verbal dominant questionnaire, which was distributed to 520 students at UIN Maulana Malik Ibrahim Malang using random sampling techniques. The results of the research show that the level of linguistic verbal intelligence of UIN Maulana Malik Ibrahim Malang students has a value of 103.92 in the sufficient category, where 0.38% of UIN Maulana Malik Ibrahim Malang students have linguistic verbal intelligence in very superior category, 43,27% have linguistic verbal intelligence in the high category, and 39,42% have linguistic verbal intelligence in the sufficient category. This shows that students' readiness to absorb Arabic language material is closely related to their linguistic verbal intelligence. Meanwhile, the results of research on the most dominant linguistic verbal dominant possessed by students are that 83.65 of students are able to use imaginative reasoning when writing or speaking, 83.19 of students are able to describe an object or event well, 78.15 of students try to tell good stories about many things, 76.88%of students read a text first and store it in memory before writing and speaking, and 76.27 of students like to talk with humor. Verbal linguistic intelligence contributes to Arabic language learning through verbal attraction, concept formation, and logical thinking, which helps students analyze the meaning of sentences, construct arguments, and solve language problems, such as understanding Arabic statements.